Processing of exposure results for composite material with the choice of their optimal composition. Issue 1 (April 2021) - Bulgakov, A; Afonin, V; Erofeeva, I; Fedortsov, V
Abstract: The article presents the results of processing a number of compositions of composite materials sustained under cyclic temperature changes, as well as changes in humidity and positive temperatures. A method is proposed for determining the optimal composition of materials, taking into account changes in such characteristics as hardness, modulus of deformation of the material and the elastic modulus of the material during exposure.